West African agriculture and climate change: A comprehensive analysis - Ghana - Nutsukpo, Delali K.; Jalloh, Abdulai; Zougmoré, Robert; Nelson, Gerald C.; Thomas, Timothy S. (International Food Policy Research Institute, 2012)
This summary note is an excerpt from the chapter on Ghana that will appear in the peer-reviewed IFPRI monograph, West African Agriculture and Climate Change: A Comprehensive Analysis